Edukasi Pelestarian Lingkungan Hidup dan Penghematan Air - Madonna, Sandra; Hermiyetti, Hermiyetti; Dewi Meilasari Sugiana, Astrid; Made Indradjaja Brunner, I (LPkM Universitas Bakrie, 2024)
Wasting clean water in society worsens the shortage of water and makes it harder to access. To address this, it’s important to promote water-saving habits and boost community involvement in protecting the environment. The clean water crisis has also been felt by the community of the Majelis Taklim Nurul Qolbi. The Majelis Taklim Nurul Qolbi, an association of blind people in Tangerang City, has also faced water shortages, especially during dry seasons and large gatherings. Community Service Activities have been carried out to overcome this problem by using technological and social approaches. The technological approach is to install 4 ablution water flow limiters at the Nurul Qolbi Musala. The social approach is to provide socialization to the community, especially the congregation at the Majelis Taklim Nurul Qolbi to save water, especially for ablution. The result of this community service activity is the application of appropriate technology from water flow limiters resulting from research innovations and social activities that have been carried out previously. This activity has succeeded in saving ablution water by reducing the water flow rate by 74.6%. The water discharge before the installation of the device was around 5 L/minute and after the installation of the device the water flow decreased to 1.27 L/minute. The results of this community service activity have given the congregation awareness to preserve the environment by carrying out energy efficiency and water conservation, and spreading the culture of saving water in the surrounding environment.